The causal relationship between financial development and investment: A review of related empirical literature - Brian Muyambiri; Nicholas M. Odhiambo (Comparative Economic Research. Central and Eastern Europe, 2018)
This article reviews the theoretical and empirical literature on the causal relationship between financial development and investment. Based on the literature considered, it can be concluded that there is little consensus to date on the direction of causality between financial development and investment. The study concludes that most of the research done on the causal relationship between financial development and investment is highly skewed towards assessing the causal relationship between the bank-based side of financial development, as compared to the market-based side of financial development. Given the number of studies assessed, the causal relationship between financial development and investment appears to be inconclusive, at best. Moreover, the study shows that the relationship between these two macroeconomic variables seems to differ from country to country; it is dependent on the proxies used to measure the level of financial development, as well as the methodology employed.
Keywords: E44; G21; O16; 330; Bank-based financial development; Causality; Investment; Market-based financial development